Production of volatiles relation to bread aroma in flour-based fermentation with yeast - Nicin, Ramazan Tolga; Ozdemir, Nilgun; Simsek, Omer; Con, Ahmet Hilmi (ELSEVIER SCI LTD, 2022)
The aim of this study is to produce a bread aroma mixture in flour-based fermentation that can potentially be added in bread dough forming after selection of yeast strains and optimization of the fermentation conditions. S. cerevisiae PFC121 produced bread aroma compounds in higher amounts compared to other 20 strains. Also, this strain provided a more balanced volatiles in bread samples that gained consumer appreciation. When the PLS analysis were evaluated, 3-methyl-1-butanol, 2-phenylethyl alcohol, nonanal, and benzaldehyde were closely related with the whole wheat flour. Conversely, 2-methyl-1-propyl acetate, and 2-methyl-1-propanol were observed to be correlated with the fermentation temperature. PCA showed that 20 degrees C fermentation temperature was effective on the accumulation of benzaldehyde and nonanal. Extending the fermentation time increased alcohol and ester accumulation. In conclusion, S. cerevisiae PFC121 is a potential strain to produce bread related volatiles at the fermentation conditions that are wheat flour, 30 degrees C, 6 pH and 48-h.
Keywords: Bread volatiles; S. cerevisiae; Fermentation; Bread-flavor; PCA; WHEAT BREAD; SACCHAROMYCES-CEREVISIAE; QUALITY; PATHWAY; CRUMB; Chemistry; Food Science & Technology; Nutrition & Dietetics